(untitled) - Esposito, Anthony (Upper Saddle River, New Jersey, 1997)
This book introduction to fluid power, properties of hydraulic fluids, energy and power in hydraulic systems....
Keywords: Fluid mechanics,Fluid power technology,Water-power